Classical Influences on 'Cantos de la batalla ausonia' by Pedro de Acosta Perestrello (Minerva, 2019)
This article offers an initial approach to Cantos de la batalla ausonia, an unpublished epic poem composed in Castilian by Portuguese poet Pedro de Acosta Perestrello after the Battle of Lepanto (1571). The paper aims to shed light on this elusive figure and his work and, most importantly, to demonstrate the classical nature of the Cantos’ epic structure.
Keywords: Cantos de la batalla ausonia; Pedro de Acosta; epic poetry; Battle of Lepanto; Renaissance